2001
DOI: 10.1161/hs1201.100209
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Ischemic Stroke Subtypes According to TOAST Criteria

Abstract: Background and Purpose-The purpose of this study was to determine the incidence, recurrence, and long-term survival rates of ischemic stroke subtypes by a mechanism-based classification scheme (Trial of ORG 10172 in Acute Stroke Treatment, or TOAST). Methods-We identified all 583 residents of the city of Erlangen, Bavaria, Germany, with a first ischemic stroke between 1994 and 1998. Multiple overlapping sources of information were used to ensure completeness of case ascertainment. The cause of ischemic stroke … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

40
395
12
16

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,116 publications
(463 citation statements)
references
References 40 publications
40
395
12
16
Order By: Relevance
“…This is in line with recent studies on young and middle‐aged patients 5, 17, while others have observed a further increase in small‐vessel occlusion at older ages 22. Large‐artery atherosclerosis followed a similar time course as small‐vessel occlusions.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This is in line with recent studies on young and middle‐aged patients 5, 17, while others have observed a further increase in small‐vessel occlusion at older ages 22. Large‐artery atherosclerosis followed a similar time course as small‐vessel occlusions.…”
Section: Discussionsupporting
confidence: 91%
“…Large‐artery atherosclerosis followed a similar time course as small‐vessel occlusions. This corresponds to that of other stroke populations 18, 22. However, while some studies have observed higher proportions of large‐artery atherosclerosis earlier in life 23, 24, our population shows that large‐artery atherosclerosis appears in the 3rd decade, but was not a common finding before the 5th decade and thereafter increased until the 8th decade before decreasing again.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Ischemic stroke subtypes were categorized using the TOAST (Trial of Org 10172 in Acute Stroke Treatment) criteria. 11 All patients were offered regular follow-up at our clinic. At each follow-up visit, assessment of vascular risk factors was determined as well as any intervention to optimize their control.…”
Section: Data Collectionmentioning
confidence: 99%
“…In population‐based studies, about 30% of IS are caused by cardiac diseases 2, 3. However, there is accumulating evidence that this relationship is not monodirectional and cerebrovascular disorders can conversely alter cardiovascular and autonomic function 4, 5, 6.…”
mentioning
confidence: 99%